Variations in airborne pollen in central and south-western Spain in relation to the distribution of potential sources. Issue 3 (4th May 2017) - Maya Manzano, José María; Fernández Rodríguez, Santiago; Vaquero Del Pino, Consolación; Gonzalo Garijo, Ángela; Silva Palacios, Inmaculada; Tormo Molina, Rafael; Moreno Corchero, Alfonsa; Cosmes Martín, Pedro Miguel; Blanco Pérez, Rosa Miriam; Domínguez Noche, Carmen; Fernández Moya, Luis; Alfonso Sanz, Juan Vicente; et al.
Abstract: The present study seeks to compare daily and hourly airborne pollen concentrations at eight different stations in Castilla-La Mancha (central Spain) and Extremadura (south-western Spain) and assess pollen distribution sources. Sampling stations were located 69–440 km apart in a straight line in Albacete, Toledo, Talavera de la Reina and Ciudad Real in Castilla-La Mancha, and in Badajoz, Plasencia, Santa Amalia and Zafra in Extremadura. Airborne pollen was collected using Hirst-type volumetric spore traps. Quercus was the most abundant pollen type at all stations except for Ciudad Real, where Olea pollen predominated. Comparisons of daily data between pairs of stations revealed statistically significant positive correlations in all cases for Poaceae and Olea . Comparisons of hourly data between stations indicated greater differences than daily data. Analysis of correlation coefficients and straight-line distances between stations revealed a strong negative correlation. Analysis of total airborne pollen data for the eight sampling stations suggests that airborne pollen concentrations decrease from west to east and from south to north, partly reflecting dominant wind patterns. A clear correlation was observed between airborne pollen concentrations and the surface area covered by olive crops in a 50 km radius around the sampling stations.